Determine the value of a real constant c, given that:
y
∫(ln p)*(1+p)-1 dp = g(y)
1
and, g(e
c) + g(e
-c) = c
3/12
where ln x denotes the
natural logarithm of x.
from the fundamental theorem of calculus we have that
g'(x)=Ln(x)/(x+1) (1)
now if we differentiate g(e^x)+g(e^-x)=x^3/12 in terms of x we get
e^x * g'(e^x) - e^-x * g'(e^-x)=x^2/4 (2)
now from (1) we have
g'(e^x)=x/(e^x + 1) and g'(e^-x)=-x/(e^-x + 1)
substituting these into (2) we have
x*e^x/(e^x+1)+x*e^-x/(e^-x+1)=x^2/4
now we have a factor of x on both sides so right off we have a solution of x=0 factoring the x we are left with
e^x/(e^x+1) + e^-x/(e^-x+1)=x/4
now when we simplify the left side we end up with 1 thus
x/4=1 x=4 is our other solution
thus the 2 values for c are c=0 and c=4
|
Posted by Daniel
on 2008-01-09 09:44:22 |